Development of a Plastic Waste Educational Learning Platform to Enhance Environmental Awareness of 21st Century Teacher Candidates at Syiah Kuala University - Maqfirah, Maqfirah; Sulastri*, Sulastri; Syukri, Muhammad; Shahali, Edi Hafizan Mohd; Rahmatan, Hafnati (Jurnal IPA & Pembelajaran IPA, 2025)
The increasingly complex problem of plastic waste needs to be addressed with more creative educational strategies so that people become more aware of the importance of preserving the environment. This study aims to describe the level of environmental awareness among FKIP students at Syiah Kuala University as future 21st-century teachers, covering knowledge, attitudes, and behavior, and to measure the effectiveness of learning interventions in increasing students' environmental awareness. This research uses a quantitative descriptive research method with initial data collection. The instruments used included a questionnaire that had been validated by experts to ensure data validity and reliability, and the test results showed that the instrument was suitable for use in the study. The research results indicate that the overall level of environmental awareness among students is still in the moderate category. A total of 58.99% of students' knowledge falls into the very low category, and 46.07% of students' attitudes are also in the same category. Meanwhile, in terms of behavior, 48.88% of students actually showed a high category. This finding indicates an imbalance between the cognitive, affective, and conative aspects of students' environmental awareness. To measure the effectiveness of awareness-raising efforts, a post-test was also conducted after the learning intervention, which showed a significant improvement, with the average knowledge score of students reaching 79%, attitudes 85%, and behavior 89%. Therefore, a strategy is needed to improve the quality of education thru stronger integration into the environmental education curriculum